PENGARUH PROFITABILITAS, CAPITAL INTENSITY DAN CORPORATE GOVERNANCE TERHADAP TAX AVOIDANCE - Pramaiswari, Gelia Ayu; fidiana, fidiana (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2022)
The purpose of this study is to investigate how profitability, capital intensity, and corporate governance affect tax avoidance. The formulation of the problem in this study is whether there is an influence between profitability, capital intensity, independent commissioners, institutional ownership, and the audit committee on tax avoidance listed on the Indonesia Stock Exchange using the purposive sampling method, namely the selection of samples with criteria determined by the researcher. The population used in this study are manufacturing companies in the food and beverage sector listed on the Indonesia Stock Exchange for the 2017-2020 period. This type of research is quantitative research by processing secondary data obtained on the Indonesia Stock Exchange. The number of research samples is 15 companies. Multiple linear analysis using the SPSS 22 version is the data analysis technique used. The results show that the variables of profitability, capital intensity, institutional ownership, and audit committee have a positive effect on tax avoidance, while independent commissioners have no effect on tax avoidance because not all independent commissioners can show their independence.